The Transcription Factor Elf3 Is Essential for a Successful Mesenchymal to Epithelial Transition - Burcu Sengez; Ilkin Aygün; Huma Shehwana; Neslihan Toyran; Sanem Tercan Avci; Ozlen Konu; Marc P. Stemmler; Hani Alotaibi (Cells, 2019)
The epithelial to mesenchymal transition (EMT) and the mesenchymal to epithelial transition (MET) are two critical biological processes that are involved in both physiological events such as embryogenesis and development and also pathological events such as tumorigenesis. They present with dramatic changes in cellular morphology and gene expression exhibiting acute changes in E-cadherin expression. Despite the comprehensive understanding of EMT, the regulation of MET is far from being understood. To find novel regulators of MET, we hypothesized that such factors would correlate with Cdh1 expression. Bioinformatics examination of several expression profiles suggested Elf3 as a strong candidate. Depletion of Elf3 at the onset of MET severely impaired the progression to the epithelial state. This MET defect was explained, in part, by the absence of E-cadherin at the plasma membrane. Moreover, during MET, ELF3 interacts with the Grhl3 promoter and activates its expression. Our findings present novel insights into the regulation of MET and reveal ELF3 as an indispensable guardian of the epithelial state. A better understanding of MET will, eventually, lead to better management of metastatic cancers.